2013
DOI: 10.1371/journal.pone.0068735
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Versatility of Aspergillus flavus during Maize Exploitation

Abstract: Aspergillus flavus is a cosmopolitan fungus able to respond to external stimuli and to shift both its trophic behaviour and the production of secondary metabolites, including that of the carcinogen aflatoxin (AF). To better understand the adaptability of this fungus, we examined genetic and phenotypic responses within the fungus when grown under four conditions that mimic different ecological niches ranging from saprophytic growth to parasitism. Global transcription changes were observed in both primary and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 66 publications
0
42
0
Order By: Relevance
“…Some other genes have also been found to affect either fungal growth or infection of the host, such as α-amylase (Woloshuk et al, 1997) and alkaline protease ). In addition, many other studies have focused on the expression of A. flavus genes during saprophytic growth to parasitism or during infection of maize kernels (Reese et al, 2011;Reverberi et al, 2013). Reverberi et al (2013) found that at least one member of a Pth11p-like protein receptor family is strongly up-regulated in inoculated maize kernels.…”
Section: Host Induced Gene Silencing Strategy To Enhance Maize Resistmentioning
confidence: 99%
“…Some other genes have also been found to affect either fungal growth or infection of the host, such as α-amylase (Woloshuk et al, 1997) and alkaline protease ). In addition, many other studies have focused on the expression of A. flavus genes during saprophytic growth to parasitism or during infection of maize kernels (Reese et al, 2011;Reverberi et al, 2013). Reverberi et al (2013) found that at least one member of a Pth11p-like protein receptor family is strongly up-regulated in inoculated maize kernels.…”
Section: Host Induced Gene Silencing Strategy To Enhance Maize Resistmentioning
confidence: 99%
“…Subsequent to this, the examination of other SM gene clusters using customized microarrays were reported 8,29,49,50) . An early effort at this was by Georgianna et al 8) whereby a collection of microarray data from 28 different treatments was used to comprehensively associate cluster expression patterns depending on treatment and environmental conditions.…”
Section: -1 Microarray Technologymentioning
confidence: 99%
“…In 2013, Reverberi et al 49) examined 24 SMURF-identified gene clusters that were described to be up or down regulated in two separate comparisons. In the first, A. flavus grown in liquid media with and without autoclaved maize kernels indicated up regulation of what is now known to be the gene clusters producing a pyrazinone (cluster 11), aflatrem (cluster 15), leporins (cluster 23), and down regulation of the AF (cluster 54) cluster.…”
Section: -1 Microarray Technologymentioning
confidence: 99%
“…In addition, detoxifying enzymes such as glutathione-S-transferase (GST) and pathogenesis-related proteins such as PR-10 can also be used to screen for pathogen resistance or abiotic stress tolerance based on their respective biological activities [15,55,56]. Genomic and proteomic expression studies during the infection process have indicated that oxidative stress tolerance is vital to adaptive changes in fungal biology during infection [57]. Additional studies have also shown that maize lines with known resistance to drought and aflatoxin contamination are more recalcitrant to oxidative stress due to more stably expressed antioxidant components than susceptible lines [25].…”
Section: Biomarkersmentioning
confidence: 99%